Changes in oral health related quality of life and its associated factors in individuals with brain injury - Kothari, Simple F.; Nascimento, Gustavo G.; De Caxias, Fernanda P. [UNESP]; Jakobsen, Mille B.; Nielsen, Jørgen F.; Kothari, Mohit (Taylor & Francis, 2021)
Purpose: To evaluate changes in oral health-related quality of life (OHRQoL) and associated factors in individuals with acquired brain injury (ABI) during hospitalization. Methods: Forty-six individuals with ABI were examined at week 1 and 5 of hospitalization. OHRQoL was recorded through Oral Health Impact Profile-14 (OHIP-14), clinical oral examinations were conducted, while orofacial health-related ‘motor’ and ‘cognitive’ scores were retrieved from patients’ e-journal. Association between variables were investigated using factor analysis and multilevel regression modeling. Results: There were no significant differences in the OHIP-14 scores between week 1 and 5. Factors analysis revealed two OHIP-14 domains, ‘psychosocial’ and ‘physica‘. Individuals who improved their cognitive skills over study period and those with ‘severe’ periodontitis at baseline had increased scores of OHIP-14 ‘psychosocial’ domain. Individuals who improved orofacial health-related ‘motor’ skills over study period had decreased ‘physical’ domain scores. Increased cognition over study period, current smoking and dental calculus were associated with increased ‘physical’ domain. Conclusions: The OHRQoL was poor both at week 1 and 5. Individual’s cognitive and motor skills as well as their oral health status influenced their OHRQoL. Thus, individual’s awareness and involvement in addition to oral care seem to be imperative in improving the OHRQoL in neurorehabilitation setting.
Keywords: Acquired Brain Injury; neurological Rehabilitation; oral Health; periodontitis; quality of Life